Initial cognitive decline is associated with cortical thinning in early Parkinson disease. - Pereira, Joana B; Svenningsson, Per; Weintraub, Daniel; Brønnick, Kolbjørn; Lebedev, Alexander; Westman, Eric; Aarsland, Dag (Neurology, 2014)
Objectives: Our aim was to assess cortical thickness in a large multicenter cohort of drug-naive patients with early Parkinson disease (PD), with and without mild cognitive impairment (MCI), and explore the cognitive correlates of regional cortical thinning.Methods: One hundred twenty-three newly diagnosed patients with PD and 56 healthy controls with 3-tesla structural MRI scans and complete neuropsychological assessment from the Parkinson's Progression Markers Initiative were included. Modified Movement Disorders Society Task Force level II criteria were applied to diagnose MCI in PD. FreeSurfer image processing and analysis software was used to measure cortical thickness across groups and the association with cognitive domains and tests.Results: In patients with MCI, atrophy was found in temporal, parietal, frontal, and occipital areas compared with controls. Specific regional thinning in the right inferior temporal cortex was also found in cognitively normal patients. Memory, executive, and visuospatial performance was associated with temporoparietal and superior frontal thinning, suggesting a relationship between cognitive impairment and both anterior and posterior cortical atrophy in the whole patient sample.Conclusions: These findings confirm that MCI is associated with widespread cortical atrophy. In addition, they suggest that regional cortical thinning is already present at the time of diagnosis in patients with early, untreated PD who do not meet the criteria for MCI. Together, the results indicate that cortical thinning can serve as a marker for initial cognitive decline in early PD.